Using automation to manage donor engagement and fine-tune supply and demand during the first year of the COVID-19 pandemic. (August 2022) - Pina, Theresa; Lewis, Marc; Garrison, Charity; Razatos, Anna
Abstract: Background: COVID-19 disrupted blood center operations starting March 2020 and continues to affect donor presentation and blood availability today. The industry mobilized significant resources to collect COVID-19 convalescent plasma (CCP) to treat COVID-19 patients. At the same time, blood centers continued to collect platelets, plasma, and red blood cells (RBCs) to meet the needs of non-COVID-19 patients. The purpose of this study was to quantify how automation was used to fine-tune supply and demand and increase donor engagement during the first year of the pandemic. Methods: This was a single-center retrospective study of blood collection and donor presentation at a mid-sized US blood center. Data was evaluated from January 1, 2020 through March 31, 2021. Parameters evaluated included donor presentation, platelets per procedure, concurrent RBC and plasma collections per procedure, operator compliance, total donor appointment count, and donor frequency. Results: With the cancelation of mobile blood drives, fixed sites increased total apheresis procedures by 37% and increased turns per bed by 46% whereas less products were collected per donor. By collecting only what was needed, platelet expiration rate decreased from 6.8% (pre-pandemic) to less than 4%. Donor engagement as measured by donor frequency increased from 1.6 in January 2020 to 1.8 in March 2021. Conclusions: Using technological advances such as automated blood collection and information systems, the blood center improved donor engagement and avoided collecting a surplus of any one type of blood product over the course of the pandemic